Energy retrofit and climate adaptive design of dwellings in the hot arid climate: Trends and future challenges - Aldhaher, Dunya Abdulazeez Gheni; Selçuk, Semra Arslan (Center of Biomass & Renewable Energy (CBIORE), 2024)
As long as buildings face various climate change impacts in recent decades, such as increased heat, particularly in the residential sector. Therefore, energy retrofit, and climate-adaptive designs may contribute significantly to climate change mitigation and adaptation strategies. At the same time, these strategies do not only improve the sustainability of dwellings/houses/residences but also contribute to broader goals of increasing energy efficiency, reducing environmental impact, offering economic benefits, and enhancing the community's resilience in the challenges they face impact from the effects of climate change. This study aims to examine and present the development of energy retrofitting, energy efficiency and climate-adaptive design for dwellings/ residential buildings in hot weather publications through bibliometric research. The research has been examined within the Web of Science™ Core Collection (W.O.S.) online database spanning from 2012 to November 2023 by using the